Interest rate policy of the Central Bank in the implementation of development-oriented credit relations and economic growth - G. Y. Tsukova (Путеводитель предпринимателя, 2020)
The article presents an analysis of interest rate policy of the Central Bank of the Russian Federation in promoting economic growth through the development of credit relations.